(untitled) (International journal of artificial intelligence, 2025)
This article explores various types of engines used in modern transportation, including internal combustion engines, electric motors, and hybrid systems. It discusses their operational principles, applications, and significance in shaping contemporary mobility while addressing environmental and technological advancements.